Use of cyber-weapons under international law - Ruško, Roberts (Riga Graduate School of Law, 2021)
The paper attempts to provide an answer to the designated research question to determine whether the use of cyber-weapons could potentially amount to jus ad bellum, under international law, by looking through the possible means for states to resort to war, what exactly constitutes use of force and whether the use of cyber-weapons, under the right circumstances be considered as use of force. Throughout the paper the author also looks at whether cyber-weapons could be equivalent to weapons of mass destruction, and their comparative differences in their definitions and properties, that helped analyze the potential of cyber-weapons to be considered as weapons of mass destruction. The paper also attempts to provide an insight on the difficulties arising for the development of a cyber-weapon treaty, which mainly revolve around the contemporary global political situation and the complications caused by the nature of such weapons, such as their traceability, and possible possession by non-state actors
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Cyberweapons